Migracje w kształtowaniu krajobrazu społecznego polskich miast - Isański, Jakub (Człowiek i Społeczeństwo, 2014)
Probably never before in history have Poles had so many possibilities of social mobility as today. The destinations of most of those who decide to start their migration within the country are confined to the largest urban areas usually. Their motivation is usually a desire to improve the quality of their life, and that means to try to find a better place to live and work. Urban areas attract people with the promise of finding a job, or better lifestyle, as well as educational opportunities. In carrying out their intentions, migrants contribute to the growth of the urban population (de facto preventing them from depopulation), economic development and cultural heritage. This text is an attempt to look at the phenomenon of migration in recent years and its impact on the transformation of the social land-scape of Polish cities.